Software Analytics for Incident Management of Online Services: An Experience Report - Lou, Jian-Guang; 林庆维, Qingwei Lin; Ding, Justin (ASE, 2013)
As online services become more and more popular, incident management has become a critical task that aims to minimize the service downtime and to ensure high quality of the provided services. In practice, incident management is conducted through analyzing a huge amount of monitoring data collected at runtime of a service. Such data-driven incident management faces several significant challenges such as the large data scale, complex problem space, and incomplete knowledge. To address these challenges, we carried out two-year software-analytics research where we designed a set of novel data-driven techniques and developed an industrial system called the Service Analysis Studio (SAS) targeting real scenarios in a large-scale online service of Microsoft. SAS has been deployed to worldwide product datacenters and widely used by on-call engineers for incident management. This paper shares our experience about using software analytics to solve engineers’ pain points in incident management, the developed data-analysis techniques, and the lessons learned from the process of research development and technology transfer.